2018
DOI: 10.1080/07347332.2018.1443192
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty as the vulnerability factor among parents of childhood cancer survivors: A 3-month follow-up study

Abstract: Parents who are intolerant of uncertainty are at risk to display dysfunctional behaviors over time. Sensitizing health care professionals to the identification of this factor and its associated difficulties is essential for the implementation of efficient intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Moreover, working mothers realized that their everyday life and the child's physical condition had recovered. According to previous studies (Boman et al, 2013;Vander Haegen & Etienne, 2018;Wikman et al, 2018), mothers experience anxiety and uncertainty after discharge, such as worrying about the recurrence of cancer, the onset of late effects and symptoms of posttraumatic stress. However, because of the reduced frequency of outpatient visits and the return of their child to school, some mothers return to work despite having psychological problems.…”
Section: Post-treatment Psychological Support For Mothersmentioning
confidence: 99%
“…Moreover, working mothers realized that their everyday life and the child's physical condition had recovered. According to previous studies (Boman et al, 2013;Vander Haegen & Etienne, 2018;Wikman et al, 2018), mothers experience anxiety and uncertainty after discharge, such as worrying about the recurrence of cancer, the onset of late effects and symptoms of posttraumatic stress. However, because of the reduced frequency of outpatient visits and the return of their child to school, some mothers return to work despite having psychological problems.…”
Section: Post-treatment Psychological Support For Mothersmentioning
confidence: 99%
“…If through their participation in PRISM families became aware of a treatment option but then encountered barriers to access, this could cause psychological distress and potentially negatively impact patient QoL. Related to this, uncertainty is known to be psychologically challenging for families [ 74 , 75 ] and it is possible the precision medicine process increased the uncertainty patients and families faced. The identification of pathogenic and likely pathogenic germline variants (identified in 16.2% of the first 247 PRISM patients [ 26 ]), with implications for the patient and their family, may also have impacted patient QoL.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the cancer experience can trigger a prolonged state of elevated alertness, which may result in increased worries, anxiety, and negative emotions 14 . Additionally, intolerance of uncertainty may contribute to a vicious cycle of hypervigilance and thereby continuous distress 17 . Several studies found elevated levels of anxiety in parents many years after cancer diagnosis of their child 15,18,19 …”
Section: Introductionmentioning
confidence: 99%
“…14 Additionally, intolerance of uncertainty may contribute to a vicious cycle of hypervigilance and thereby continuous distress. 17 Several studies found elevated levels of anxiety in parents many years after cancer diagnosis of their child. 15,18,19 Previous studies have shown that a cancer diagnosis of a child can affect many aspects of parents' lives in the long-term, for example, their relationship, financial situation, and involvement in healthcare of child.…”
Section: Introductionmentioning
confidence: 99%